SUDDEN ANOSMIA - HIDDEN INTIMATION OF NOVEL CORONAVIRUS - Abbas, Sana; Rafique, Aisha; Akram, Amjad; Zafar, Omer; Khan, Basit Mehmood; Abbas, Beenish (Pakistan Armed Forces Medical Journal, 2020)
The coronavirus infection 2019 (COVID-19) is a progressing viral pandemic. Adverse impacts related to COVID19 are usually includes sore throat, cough, fever and dyspnea. Anosmia emerged as newer reported symptom however, recognition awaited from the World Health Organization (WHO) and Center for Infection Control and Prevention (CDC). This case series features an instance of isolated abrupt presentation of anosmia as amanifestation of COVID-19 between two young males with parallelism of smoking and modest disease manifestation. Loss of smell is demonstrative of COVID-19 disease and has significant ramifications with regards to healthcare workers working close to infected therefore has increased susceptibility.